The CSF1R-Microglia Axis Has Protective Host-Specific Roles During Neurotropic Picornavirus Infection - Sanchez, John Michael S.; DePaula-Silva, Ana Beatriz; Doty, Daniel J.; Hanak, Tyler J.; Truong, Amanda; Libbey, Jane E.; Fujinami, Robert S. (Frontiers in Immunology, 2021)
Viral encephalitis is a major cause of morbidity and mortality, but the manifestation of disease varies greatly between individuals even in response to the same virus. Microglia are professional antigen presenting cells that reside in the central nervous system (CNS) parenchyma that are poised to respond to viral insults. However, the role of microglia in initiating and coordinating the antiviral response is not completely understood. Utilizing Theiler’s murine encephalomyelitis virus (TMEV), a neurotropic picornavirus, and PLX5622, a small molecule inhibitor of colony-stimulating factor 1 receptor (CSF1R) signaling that can deplete microglia in the CNS; we investigated the role of the CSF1R-microglia axis in neurotropic picornavirus infection of C57BL/6J and SJL/J mice. These mouse strains differ in their ability to clear TMEV and exhibit different neurological disease in response to TMEV infection. CSF1R antagonism in C57BL/6J mice, which normally clear TMEV in the CNS, led to acute fatal encephalitis. In contrast, CSF1R antagonism in SJL/J mice, which normally develop a chronic CNS TMEV infection, did not result in acute encephalitis, but exacerbated TMEV-induced demyelination. Immunologically, inhibition of CSF1R in C57BL/6J mice reduced major histocompatibility complex II expression in microglia, decreased the proportion of regulatory T cells in the CNS, and upregulated proinflammatory pathways in CNS T cells. Acute CSF1R inhibition in SJL/J mice had no effect on microglial MHC-II expression and upregulated anti-inflammatory pathways in CNS T cells, however chronic CSF1R inhibition resulted in broad immunosuppression. Our results demonstrate strain-specific effects of the CSF1R-microglia axis in the context of neurotropic viral infection as well as inherent differences in microglial antigen presentation and subsequent T cell crosstalk that contribute to susceptibility to neurotropic picornavirus infection.